A pigeonpea gene confers resistance to Asian soybean rust in soybean - Kawashima, Cintia G; Guimarães, Gustavo Augusto; Nogueira, Sônia Regina; MacLean, Dan; Cook, Doug R; Steuernagel, Burkhard; Baek, Jongmin; Bouyioukos, Costas; Melo, Bernardo do V. A.; Tristão, Gustavo; Oliveira, Jamile Camargos de; Brommonschenkel, Sérgio H; et al. (Nature Biotechnology, 2016)
Asian soybean rust (ASR), caused by the fungus Phakopsora pachyrhizi, is one of the most economically important crop diseases, but is only treatable with fungicides, which are becoming less effective owing to the emergence of fungicide resistance. There are no commercial soybean cultivars with durable resistance to P. pachyrhizi, and although soybean resistance loci have been mapped, no resistance genes have been cloned. We report the cloning of a P. pachyrhizi resistance gene CcRpp1 (Cajanus cajan Resistance against Phakopsora pachyrhizi 1) from pigeonpea (Cajanus cajan) and show that CcRpp1 confers full resistance to P. pachyrhizi in soybean. Our findings show that legume species related to soybean such as pigeonpea, cowpea, common bean and others could provide a valuable and diverse pool of resistance traits for crop improvement.
Keywords: Pigeonpea gene; Asian soybean